ESTIMASI POTENSI TEGAKAN DENGAN PEMANFAATAN PENGINDERAAN JAUH DI PT. PRIMA MULTIBUANA KABUPATEN BANJAR - Helmi Didi Yahya; Mufidah Asy'ari; Wahyuni Ilham (Universitas Lambung Mangkurat, 2020)
High cost in doing the census method in forest inventory activities, therefore required the existence of a method of using remote sensing to simplify data retrieval in the determination of inventory. The purpose of the research to estimate the potential of the forest in PT Multibuana Prima by using Landsat 8 transformation of NDVI (Normalized Different Vegetation Index) and to test the accuracy of Landsat 8 in estimating the potential of the forest. The method used is the stratified sampling that supported by remote sensing data e.g. image of Landsat and aerial UAV (Unmanned Aarial Vehicle) as well as verification of data in the field. Based on a linear regression analysis was obtained by the potential value of forest in PT Multibuana Prima, range between 120-446 m3/ha, with an accuracy of 37.5% imagery truth.Keywords:Remote Sensing;Landsat 8;Normalized Diffrerence Vegetation Index (NDVI); Unmanned Aerial Vehicle (UAV)